Rice Flowering Locus T 1 plays an important role in heading date influencing yield traits in rice - Zhu, Yu-Jun (Sci Rep, 2017)
Important role of flowering genes in enhancing grain productivity in rice has become well recognized for a number of key genes regulating the florigen production, but little has been known for the two florigen genes themselves. In this study, pleiotropism of Rice Flowering Locus T 1 (RFT1), one of the two florigen genes in rice, was firstly evaluated using near isogenic lines (NILs) carrying RFT1 alleles from the indica rice cultivars Zhenshan 97 (ZS97) and Milyang 46, respectively, and then determined by transformation of the RFT1 (ZS97) allele into a japonica rice variety, Zhonghua 11. The RFT1 (ZS97) allele was shown to delay heading and increase plant height, grain weight, grain number and grain yield, indicating that RFT1 plays an important role in the growth and development of rice. This study has also validated the potential of using a new type of genetic resource, sequential residual heterozygotes (SeqRHs), for QTL fine-mapping. A step-by-step approach was employed for SeqRHs identification, NIL development and QTL fine-mapping. The heterozygous segments and candidate QTL regions were gradually narrowed down. Eventually, the QTL region was delimited to a 1.7 kb region containing a single gene.